High-barrier composite film and preparation method thereof
By designing a three-layer structure in a high-barrier composite film, optimizing the coating composition, and using carboxy modified polyvinyl alcohol resin and nanohydrotalcite and other materials, the problem of difficult coating thickness and poor binding force in the prior art is solved, and efficient barrier performance and recyclability are achieved.
Patent Information
- Application Number
- CN202510423509.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-07
- Publication Date
- 2025-05-06
- Estimated Expiration
- 2045-04-07
AI Technical Summary
When the existing high-barrier composite film meets the requirements of recyclability and food-grade fresh preservation barrier, the coating thickness is difficult to take into account, and PVA is prone to moisture absorption, degradation of barrier properties, and poor binding force limits its application.
The high-barrier composite film design with a three-layer structure includes the first PE layer, the high-barrier coating and the second PE layer. By optimizing the coating composition, using materials such as carboxy modified polyvinyl alcohol resin and nanohydrtalcite, combined with crosslinking agents and additives, the density and binding strength of the coating are enhanced.
It is achieved to significantly improve the barrier performance and binding force of the high-barrier composite film without increasing the coating thickness, meeting the requirements of recyclability and food-grade fresh preservation.
Smart Images

Figure CN119928380A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite films, and in particular to a high-barrier composite film and a preparation method thereof. Background Art
[0002] Recyclable plastic soft packaging is a new type of environmentally friendly packaging material, which usually requires a single material component ratio of more than 95%. When recyclable plastic soft packaging is used in food, medicine, electronic devices and other occasions that require high freshness of the contents and need to meet water and oxygen isolation conditions, it is often also necessary to have high barrier properties. Traditional high barrier soft packaging films, such as aluminized films or multi-layer co-extruded films, cannot meet the recycling indicators. Therefore, the development of plastic soft packaging films with both high barrier properties and recyclability is an important topic.
[0003] In order to meet the packaging processability, barrier properties and recyclability, coating a high barrier coating on the base film to prepare a composite film is an ideal solution. Polyvinylidene chloride (PVDC) emulsion is a polymer coating traditionally used to prepare coated barrier films. For example, the patent with patent publication number CN101654165A discloses a composite paper-plastic food packaging material using PVDC as a barrier coating. However, PVDC contains chlorine, which is toxic when burned, difficult to recycle and dispose of waste, and not environmentally friendly, and has been gradually eliminated in food packaging. Polyvinyl alcohol (PVA) is a polymer material commonly used to prepare high barrier coatings, which has the characteristics of wide sources, stable performance, excellent barrier properties, and non-toxicity. For example, the patent with patent publication number CN103382677A discloses a high barrier polyvinyl alcohol coating for liner paper coating and its preparation method. The coating is directly coated on the liner paper substrate and has good adhesion and barrier properties, but its barrier properties still have room for improvement.
[0004] In order to make the proportion of single material reach more than 95% to meet the recyclability, the coating thickness cannot be too large. The existing technical solutions are difficult to meet the food-grade preservation barrier requirements when the coating thickness is small; in addition, PVA is easy to absorb moisture, and the barrier performance drops sharply after moisture absorption; PVA and conventional packaging materials (such as polyethylene (PE)) have poor bonding strength. These shortcomings seriously limit the development and application of coated recyclable high-barrier composite films. Summary of the invention
[0005] Based on this, in order to solve one of the above problems, the present invention provides a high barrier composite film and a preparation method thereof, and the specific technical scheme is as follows: A high-barrier composite film, comprising a first PE layer, a high-barrier coating layer and a second PE layer arranged in sequence, wherein the thickness of the first PE layer and the second PE layer respectively accounts for 20% to 79% of the total thickness of the high-barrier composite film, and the thickness of the high-barrier coating layer accounts for 1% to 5% of the total thickness of the high-barrier composite film; Wherein, the first PE layer and the second PE layer both include the following raw materials in parts by weight: 30 to 80 parts of PE resin, 20 to 70 parts of carboxyl-modified polyethylene, and 0.1 to 10 parts of auxiliary materials; The high barrier coating comprises the following raw materials in parts by weight: 100 parts of carboxyl-modified polyvinyl alcohol resin, 40 to 400 parts of nano-hydrotalcite, 1 to 80 parts of carboxyl-terminated polyethylene glycol siloxane, 3 to 12 parts of a crosslinking agent and 3 to 12 parts of an auxiliary agent.
[0006] Furthermore, the melt index of the PE resin at 190° C. and 2.16 kg is in the range of 1 g / 10 min to 30 g / 10 min.
[0007] Furthermore, the carboxyl-modified polyethylene is one or more of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, acrylic acid grafted polyethylene and methacrylic acid grafted polyethylene.
[0008] Furthermore, the auxiliary materials include one or more of antioxidants, anti-ultraviolet agents, plasticizers, flame retardants, nucleating agents and inorganic fillers.
[0009] Furthermore, the weight average molecular weight of the carboxyl-modified polyvinyl alcohol resin is 60,000 g / moL-300,000 g / moL, the alcoholysis degree is 80%-99%, and the mass fraction of the carboxyl group is 0.2%-5%.
[0010] Furthermore, the nano-hydrotalcite is an inorganic nano-sheet with a layered structure, the thickness of a single sheet is 6nm-20nm, and the average diameter-to-thickness ratio of a single sheet is 150-250.
[0011] Furthermore, the weight average molecular weight of the polyethylene glycol segment of the carboxyl-terminated polyethylene glycol siloxane is 200 g / moL to 4000 g / moL; The chemical structural formula of the carboxyl-terminated polyethylene glycol siloxane is as follows: .
[0012] Furthermore, the crosslinking agent is a multifunctional aziridine crosslinking agent, and the multifunctional aziridine crosslinking agent is one or more of trimethylolpropane-tris[3-(2-methylaziridine)]propionate, trimethylolpropane-tris(3-aziridine)propionate and pentaerythritol tris(3-aziridine)propionate.
[0013] Furthermore, the auxiliary agent includes one or more of a defoaming agent, a leveling agent, an antioxidant, an anti-hydrolysis agent, and a UV absorber.
[0014] In addition, the present invention provides a method for preparing a high barrier composite film, the preparation method comprising the following steps: The raw materials for preparing the first PE layer are mixed evenly, melt-blended and extruded into granules in a twin-screw extruder to obtain a first PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a first PE layer base film; The raw materials for preparing the second PE layer are mixed uniformly, melt-blended and extruded into granules in a twin-screw extruder to obtain a second PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a second PE layer base film; Dispersing a carboxyl-modified polyvinyl alcohol resin, a crosslinking agent and an auxiliary agent in an appropriate amount of water to obtain a carboxyl-modified polyvinyl alcohol aqueous dispersion; then dispersing nano-hydrotalcite and carboxyl-terminated polyethylene glycol siloxane in an appropriate amount of water, stirring at 50° C. to 80° C. for 6 h to 24 h to obtain a carboxyl-modified nano-hydrotalcite aqueous dispersion, and cooling to room temperature; and then adding the carboxyl-modified nano-hydrotalcite aqueous dispersion to the carboxyl-modified polyvinyl alcohol aqueous dispersion under stirring, adjusting the solid content within the range of 3% to 15%, to obtain a high barrier coating; The high barrier coating is coated on one side of the first PE layer base film and / or the second PE layer base film, and then the side coated with the high barrier coating is laminated, hot air dried at 60°C~105°C, and then aged at 45°C~80°C for 48h~72h to obtain a high barrier composite film.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention optimizes the raw materials for preparing the high-barrier coating, uses carboxyl-modified polyvinyl alcohol resin and nano-hydrotalcite as main components, has better compactness, strengthens the barrier performance by a cross-linking agent, and adds carboxyl-terminated polyethylene glycol siloxane to modify the surface of the nano-hydrotalcite and shield its surface hydroxyl groups. At the same time, the steric effect of the polyethylene glycol macromolecular chain segment is used to inhibit the agglomeration of nanosheets and strengthen their dispersibility. The single-sheet thickness of the nano-hydrotalcite is limited to 6nm~20nm, and the average diameter-to-thickness ratio of the single sheet is 150~250, so that the coating thickness does not exceed 5% of the thickness of the high-barrier composite film, which not only meets the recyclability but also has significant barrier properties.
[0016] 2. The present invention introduces carboxyl-modified polyethylene into the raw materials for preparing the first PE layer and the second PE layer, and after corona treatment, the surface has more carboxyl functional groups, which can interact with the carboxyl-modified polyvinyl alcohol resin, carboxyl-terminated polyethylene glycol siloxane-modified nanofiller and multifunctional aziridine crosslinker in the high barrier coating, while ensuring high barrier performance, initiating the carboxyl crosslinking reaction of each component, and significantly increasing the bonding force between the first PE layer, the high barrier coating and the second PE layer. Specifically, adding a multifunctional aziridine crosslinker to initiate the reaction of the first PE layer, the high barrier coating layer and the second PE layer, so that they are bonded through chemical bonds to avoid coating peeling; initiating the reaction between the carboxyl-modified polyvinyl alcohol resin, the carboxyl-terminated polyethylene glycol siloxane and the nano-hydrotalcite, not only strengthens the mechanical strength of the high barrier coating, but also significantly improves the barrier performance of the high barrier coating, and overall solves the problem of poor bonding between the polar high barrier coating and the non-polar PE layer.
[0017] 3. The present invention provides a sandwich structure of a first PE layer, a high barrier coating and a second PE layer. The non-polar PE layer has excellent water-blocking properties. Combined with the synergistic effect of the high barrier coating, it can significantly improve moisture intrusion. In addition, after adding a multifunctional aziridine cross-linking agent to promote the cross-linking of the carboxyl-modified polyvinyl alcohol resin, the hygroscopicity of the composite film can also be significantly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the structure of a high-barrier composite film prepared in Example 1 of the present invention; Figure 2 Schematic diagram of the principle of carboxyl-terminated polyethylene glycol siloxane-modified nano-hydrotalcite in Example 1 of the present invention.
[0019] Description of reference numerals: 1-first PE layer, 2-high barrier composite layer, 3-second PE layer. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the protection scope of the present invention.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0022] A high-barrier composite film in one embodiment of the present invention comprises a first PE layer, a high-barrier coating layer and a second PE layer arranged in sequence, and the thickness of the first PE layer and the second PE layer respectively accounts for 20% to 79% of the total thickness of the high-barrier composite film, and the thickness of the high-barrier coating layer accounts for 1% to 5% of the total thickness of the high-barrier composite film; Wherein, the first PE layer and the second PE layer both include the following raw materials in parts by weight: 30 to 80 parts of PE resin, 20 to 70 parts of carboxyl-modified polyethylene, and 0.1 to 10 parts of auxiliary materials; The high barrier coating comprises the following raw materials in parts by weight: 100 parts of carboxyl-modified polyvinyl alcohol resin, 40 to 400 parts of nano-hydrotalcite, 1 to 80 parts of carboxyl-terminated polyethylene glycol siloxane, 3 to 12 parts of a crosslinking agent and 3 to 12 parts of an auxiliary agent.
[0023] In one embodiment, the PE resin has a melt index of 1 g / 10 min to 30 g / 10 min, preferably 5 g / 10 min to 20 g / 10 min, at 190° C. and 2.16 kg. The PE resin has better processing performance within this range.
[0024] In one embodiment, the PE resin is one or more of low-density polyethylene, high-density polyethylene, linear low-density polyethylene, metallocene polyethylene, ethylene-α-olefin copolymer, and bimodal polyethylene.
[0025] In one embodiment, the carboxyl-modified polyethylene is one or more of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, acrylic acid grafted polyethylene and methacrylic acid grafted polyethylene.
[0026] In one embodiment, the melt index of the carboxyl-modified polyethylene at 190° C. and 2.16 kg is in the range of 1 g / 10 min to 30 g / 10 min, preferably 5 g / 10 min to 20 g / 10 min. Within this range, the processing performance is better.
[0027] In one embodiment, the mass fraction of the carboxyl functional monomer in the carboxyl-modified polyethylene is in the range of 0.5% to 25%, and has good reactivity and processability within this range.
[0028] In one embodiment, the auxiliary materials include one or more of an antioxidant, an anti-ultraviolet agent, a plasticizer, a flame retardant, a nucleating agent and an inorganic filler.
[0029] In one embodiment, the weight average molecular weight of the carboxyl-modified polyvinyl alcohol resin is 60000 g / mol-300000 g / mol, the alcoholysis degree is 80%-99%, and the mass fraction of the carboxyl group is 0.2%-5%. The carboxyl-modified polyvinyl alcohol resin within this range has good water solubility, reactivity and storage stability.
[0030] In one embodiment, the nano hydrotalcite is an inorganic nano sheet with a layered structure, the thickness of a single sheet is 6nm~20nm, and the average diameter-thickness ratio of a single sheet is 150~250. When the thickness of a single sheet is less than 6nm, not only the raw material production cost is high, but also the strength of the composite film is affected; when the thickness of a single sheet is greater than 20nm, the dispersibility is extremely poor, which will affect the stability of the coating; when the average diameter-thickness ratio of a single sheet is less than 150, an effective barrier channel cannot be formed, and its barrier performance will be affected; when the average diameter-thickness ratio is greater than 250, the strength of the nano hydrotalcite sheet is low, it is easy to break spontaneously, and the processing cost is high.
[0031] In one embodiment, the nano hydrotalcite is one or more of magnesium aluminum hydrotalcite, aluminum nickel hydrotalcite, magnesium indium hydrotalcite, magnesium gallium hydrotalcite and zinc aluminum hydrotalcite, preferably magnesium aluminum hydrotalcite.
[0032] In one embodiment, the weight average molecular weight of the polyethylene glycol segment of the carboxyl-terminated polyethylene glycol siloxane is 200 g / moL to 4000 g / moL; The chemical structural formula of the carboxyl-terminated polyethylene glycol siloxane is as follows: .
[0033] The carboxyl-terminated polyethylene glycol siloxane can react with the surface hydroxyl groups of nano hydrotalcite to shield the surface hydroxyl groups, and the high molecular weight polyethylene glycol segment further plays a steric hindrance role, reduces the agglomeration of nano hydrotalcite, and strengthens the water dispersibility of nano sheets. The terminal carboxyl group can participate in the cross-linking reaction of the coating to increase the strength of the coating. If the molecular weight of the above polyethylene glycol segment is too small, the steric hindrance is too weak and the dispersion effect is not ideal; if the molecular weight is too large, the steric hindrance is too strong, which will affect the reaction of siloxane and hydroxyl groups.
[0034] In one embodiment, the crosslinking agent is a multifunctional aziridine crosslinking agent, and the multifunctional aziridine crosslinking agent is one or more of trimethylolpropane-tris[3-(2-methylaziridine)]propionate, trimethylolpropane-tris(3-aziridine)propionate and pentaerythritol tris(3-aziridine)propionate.
[0035] In one embodiment, the reaction formula of the multifunctional aziridine crosslinker and the carboxyl group is as follows: .
[0036] In one embodiment, the auxiliary agent includes one or more of a defoaming agent, a leveling agent, an antioxidant, an anti-hydrolysis agent, and a UV absorber.
[0037] In addition, the present invention provides a method for preparing a high barrier composite film, the preparation method comprising the following steps: The raw materials for preparing the first PE layer are mixed evenly, melt-blended and extruded into granules in a twin-screw extruder to obtain a first PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a first PE layer base film; The raw materials for preparing the second PE layer are mixed uniformly, melt-blended and extruded into granules in a twin-screw extruder to obtain a second PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a second PE layer base film; Dispersing a carboxyl-modified polyvinyl alcohol resin, a crosslinking agent and an auxiliary agent in an appropriate amount of water to obtain a carboxyl-modified polyvinyl alcohol aqueous dispersion; then dispersing nano-hydrotalcite and carboxyl-terminated polyethylene glycol siloxane in an appropriate amount of water, stirring at 50° C. to 80° C. for 6 h to 24 h to obtain a carboxyl-modified nano-hydrotalcite aqueous dispersion, and cooling to room temperature; and then adding the carboxyl-modified nano-hydrotalcite aqueous dispersion to the carboxyl-modified polyvinyl alcohol aqueous dispersion under stirring, adjusting the solid content within the range of 3% to 15%, to obtain a high barrier coating; The high barrier coating is coated on one side of the first PE layer base film and / or the second PE layer base film, and then the side coated with the high barrier coating is laminated, hot air dried at 60°C~105°C, and then aged at 45°C~80°C for 48h~72h to obtain a high barrier composite film.
[0038] In one embodiment, the melt-processed film forming includes but is not limited to the processes of blowing, casting and calendering.
[0039] By optimizing the composition of each layer in the above scheme, excellent bonding strength can be obtained as a whole. When the thickness of the coating layer is no more than 5% of the overall thickness of the composite film, it still has significant barrier properties and meets the recyclability requirements.
[0040] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0041] It should be noted that the CPVA resin described in this application is a carboxyl-modified polyvinyl alcohol resin.
[0042] Embodiment 1: A high barrier composite film having a three-layer structure, which is sequentially arranged as a first PE layer, a high barrier coating layer and a second PE layer; The first PE layer and the second PE layer both include the preparation materials described in Table 1 below, and the high barrier coating includes the preparation materials described in Table 2 below; Table 1: Raw materials for the preparation of the first PE layer and the second PE layer
[0043] Table 2: Raw materials for preparation of high barrier coating
[0044] The preparation method of the high barrier composite film in Example 1 is as follows: In the first step, the raw materials for preparing the first PE layer and the second PE layer are dried and mixed in proportion, respectively, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a PE layer mixture; then the PE layer mixture is melt cast and subjected to corona treatment to obtain a first PE layer base film and a second PE layer base film respectively; In the second step, the measured CPVA resin, crosslinking agent and auxiliary agent are dissolved / dispersed in an appropriate amount of water to obtain a CPVA aqueous dispersion. The measured nano hydrotalcite and carboxyl-terminated polyethylene glycol siloxane are dispersed in an appropriate amount of water, stirred at 80°C for 6 hours to prepare an aqueous dispersion of carboxyl-modified nano hydrotalcite, cooled to room temperature, and added to the above CPVA aqueous dispersion while stirring, and the amount of water is adjusted so that the overall solid content of the coating is 8%, to obtain a high barrier coating; In the third step, the high barrier coating is evenly coated on one side of the first PE layer base film, and then a second PE layer base film is covered on the side coated with the high barrier coating, and then dried with hot air at 95°C, and then aged at 80°C for 48 hours to obtain the high barrier composite film of this embodiment.
[0045] The total thickness of the high-barrier composite film prepared in Example 1 is 0.15 mm, the thickness of the first PE layer accounts for 48% of the total thickness of the high-barrier composite film, the thickness of the high-barrier coating accounts for 4% of the total thickness of the high-barrier composite film, and the thickness of the second PE layer accounts for 48% of the total thickness of the high-barrier composite film.
[0046] Embodiment 2: A high barrier composite film having a three-layer structure, which is sequentially arranged as a first PE layer, a high barrier coating layer and a second PE layer; The first PE layer includes the raw materials described in Table 3 below, the second PE layer includes the raw materials described in Table 4 below, and the high barrier coating includes the raw materials described in Table 5 below; Table 3: Raw materials for the preparation of the first PE layer
[0047] Table 4: Raw materials for preparation of the second PE layer
[0048] Table 5: Raw materials for preparation of high barrier coating
[0049] The preparation method of the high barrier composite film in Example 2 is as follows: In the first step, the raw materials for preparing the first PE layer and the second PE layer are dried and mixed in proportion, respectively, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a PE layer mixture; then the PE layer mixture is melt cast and subjected to corona treatment to obtain a first PE layer base film and a second PE layer base film respectively; The second step is to dissolve / disperse the measured CPVA resin, crosslinking agent and auxiliary agent in an appropriate amount of water to obtain a CPVA aqueous dispersion. The measured nano hydrotalcite and carboxyl-terminated polyethylene glycol siloxane are dispersed in an appropriate amount of water, stirred at 50°C for 16 hours to prepare an aqueous dispersion of carboxyl-modified nano hydrotalcite, and after cooling to room temperature, added to the above CPVA aqueous dispersion while stirring, and the amount of water is adjusted so that the overall solid content of the coating is 15% to obtain a high barrier coating; In the third step, the high-barrier coating is evenly coated on one side of the first PE layer base film, and then a second PE layer base film is covered on the side coated with the high-barrier coating, and then dried with hot air at 85°C and then aged at 60°C for 72 hours to obtain the high-barrier composite film of this embodiment.
[0050] The total thickness of the high-barrier composite film prepared in Example 2 is 0.15 mm, the thickness of the first PE layer accounts for 65% of the total thickness of the high-barrier composite film, the thickness of the high-barrier coating accounts for 2% of the total thickness of the high-barrier composite film, and the thickness of the second PE layer accounts for 33% of the total thickness of the high-barrier composite film.
[0051] Embodiment 3: A high barrier composite film having a three-layer structure, which is sequentially arranged as a first PE layer, a high barrier coating layer and a second PE layer; The first PE layer includes the raw materials described in Table 6 below, the second PE layer includes the raw materials described in Table 7 below, and the high barrier coating includes the raw materials described in Table 8 below; Table 6: Raw materials for preparation of the first PE layer
[0052] Table 7: Raw materials for preparation of the second PE layer
[0053] Table 8: Raw materials for preparation of high barrier coating
[0054] The preparation method of the high barrier composite film in Example 3 is as follows: In the first step, the raw materials for preparing the first PE layer and the second PE layer are dried and mixed in proportion, respectively, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a PE layer mixture; then the PE layer mixture is melt cast and subjected to corona treatment to obtain a first PE layer base film and a second PE layer base film respectively; The second step is to dissolve / disperse the measured CPVA resin, crosslinking agent and auxiliary agent in an appropriate amount of water to obtain a CPVA aqueous dispersion. The measured nano hydrotalcite and carboxyl-terminated polyethylene glycol siloxane are dispersed in an appropriate amount of water, stirred at 70°C for 24 hours to prepare an aqueous dispersion of carboxyl-modified nano hydrotalcite, and after cooling to room temperature, added to the above CPVA aqueous dispersion while stirring, and the amount of water is adjusted so that the overall solid content of the coating is 4%, to obtain a high barrier coating; In the third step, the high-barrier coating is evenly coated on one side of the first PE layer base film, and then a second PE layer base film is covered on the side coated with the high-barrier coating, and then dried with hot air at 100°C and then aged at 45°C for 72 hours to obtain the high-barrier composite film of this embodiment.
[0055] The total thickness of the high-barrier composite film prepared in Example 3 is 0.15 mm, the thickness of the first PE layer accounts for 50% of the total thickness of the high-barrier composite film, the thickness of the high-barrier coating accounts for 1% of the total thickness of the high-barrier composite film, and the thickness of the second PE layer accounts for 49% of the total thickness of the high-barrier composite film.
[0056] Embodiment 4: A high barrier composite film having a three-layer structure, which is sequentially arranged as a first PE layer, a high barrier coating layer and a second PE layer; The first PE layer and the second PE layer include the preparation materials described in Table 9 below, and the high barrier coating includes the preparation materials described in Table 10 below; Table 9: Raw materials for the preparation of the first PE layer and the second PE layer
[0057] Table 10: Raw materials for preparation of high barrier coatings
[0058] The preparation method of the high barrier composite film in Example 4 is as follows: In the first step, the raw materials for preparing the first PE layer and the second PE layer are dried and mixed in proportion, respectively, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a PE layer mixture; then the PE layer mixture is melt cast and subjected to corona treatment to obtain a first PE layer base film and a second PE layer base film respectively; The second step is to dissolve / disperse the measured CPVA resin, crosslinking agent and auxiliary agent in an appropriate amount of water to obtain a CPVA aqueous dispersion. The measured nano hydrotalcite and carboxyl-terminated polyethylene glycol siloxane are dispersed in an appropriate amount of water, stirred at 55°C for 20 hours to prepare an aqueous dispersion of carboxyl-modified nano hydrotalcite, and after cooling to room temperature, added to the above CPVA aqueous dispersion while stirring, and the amount of water is adjusted so that the overall solid content of the coating is 10%, to obtain a high barrier coating; In the third step, the high-barrier coating is evenly coated on one side of the first PE layer base film, and then a second PE layer base film is covered on the side coated with the high-barrier coating, and then dried with hot air at 60°C and then aged at 75°C for 30 hours to obtain the high-barrier composite film of this embodiment.
[0059] The total thickness of the high-barrier composite film prepared in Example 4 is 0.15 mm, the thickness of the first PE layer accounts for 36% of the total thickness of the high-barrier composite film, the thickness of the high-barrier coating accounts for 4% of the total thickness of the high-barrier composite film, and the thickness of the second PE layer accounts for 60% of the total thickness of the high-barrier composite film.
[0060] Embodiment 5: A high barrier composite film having a three-layer structure, which is sequentially arranged as a first PE layer, a high barrier coating layer and a second PE layer; The first PE layer and the second PE layer include the preparation materials described in Table 11 below, and the high barrier coating includes the preparation materials described in Table 12 below; Table 11: Raw materials for the preparation of the first PE layer and the second PE layer
[0061] Table 12: Raw materials for preparation of high barrier coating
[0062] The preparation method of the high barrier composite film in Example 5 is as follows: In the first step, the raw materials for preparing the first PE layer and the second PE layer are dried and mixed in proportion, respectively, and then put into a twin-screw extruder for melt blending, extrusion and granulation to obtain a PE layer mixture; then the PE layer mixture is melt cast and subjected to corona treatment to obtain a first PE layer base film and a second PE layer base film respectively; The second step is to dissolve / disperse the measured CPVA resin, crosslinking agent and auxiliary agent in an appropriate amount of water to obtain a CPVA aqueous dispersion. The measured nano hydrotalcite and carboxyl-terminated polyethylene glycol siloxane are dispersed in an appropriate amount of water, stirred at 80°C for 15 hours to prepare an aqueous dispersion of carboxyl-modified nano hydrotalcite, and after cooling to room temperature, added to the above CPVA aqueous dispersion while stirring, and the amount of water is adjusted so that the overall solid content of the coating is 9.6%, to obtain a high barrier coating; In the third step, the high-barrier coating is evenly coated on one side of the first PE layer base film, and then a second PE layer base film is covered on the side coated with the high-barrier coating, and then dried with hot air at 100°C, and then aged at 80°C for 65 hours to obtain the high-barrier composite film of this embodiment.
[0063] The total thickness of the high-barrier composite film prepared in Example 5 is 0.15 mm, the thickness of the first PE layer accounts for 64% of the total thickness of the high-barrier composite film, the thickness of the high-barrier coating accounts for 3% of the total thickness of the high-barrier composite film, and the thickness of the second PE layer accounts for 33% of the total thickness of the high-barrier composite film.
[0064] Comparative Example 1: Compared with Example 1, no nano-hydrotalcite was added in Comparative Example 1, and the rest was the same as Example 1.
[0065] Comparative Example 2: Compared with Example 1, the first PE layer and the second PE layer in Comparative Example 2 do not contain carboxyl-modified polyethylene, and the rest are the same as Example 1.
[0066] Comparative Example 3: Compared with Example 1, no crosslinking agent is added to the raw materials for preparing the high barrier coating in Comparative Example 3, and the rest is the same as Example 3.
[0067] Comparative Example 4: Compared with Example 1, conventional polyvinyl alcohol resin is used to replace CPVA resin in the raw materials for preparing the high barrier coating in Comparative Example 4, and the rest is the same as Example 1.
[0068] Comparative Example 5: Compared with Example 1, no carboxyl-terminated polyethylene glycol siloxane was added to the raw materials for preparing the high barrier coating of Comparative Example 5, and the rest was the same as Example 1.
[0069] Comparative Example 6: Compared with Example 1, the process in Comparative Example 6 was not subjected to corona treatment, and the rest was the same as Example 1.
[0070] Comparative Example 7: Compared with Example 1, the single-piece thickness of the nano-hydrotalcite in Comparative Example 7 is 25 nm, the single-piece average diameter-to-thickness ratio is 120, and the rest is the same as Example 1.
[0071] Comparative Example 8: Compared with Example 1, the single-piece thickness of the nano-hydrotalcite in Comparative Example 8 is 25 nm, the single-piece average diameter-to-thickness ratio is 300, and the rest is the same as Example 1.
[0072] The high barrier composite film samples of Examples 1 to 5 and the high barrier composite film comparison samples of Comparative Examples 1 to 8 were respectively subjected to performance tests according to the following methods.
[0073] Coating adhesion level: The test is conducted using the cross-cut method in accordance with the national standard GB / T 9286. The adhesion level is divided into six levels from 0 to 5, from good to bad. No less than 5 areas of the same sample are randomly selected for testing, and the lowest adhesion level is recorded as the test result.
[0074] Oxygen Transmission Rate (OTR): Tested in accordance with the test method of GB / T 19789-2021. Test temperature is 23°C and relative humidity is 0. Select 5 different areas of the sample for testing and take the average value. The lower the OTR value, the better the barrier performance.
[0075] Water vapor transmission rate (WVTR): Tested in accordance with the test method of GB / T 26253-2010. Test temperature was 23°C and relative humidity was 50%. Five different areas of the sample were selected for testing and the average value was taken. The lower the WVTR value, the better the barrier performance. The results are shown in Table 13 below.
[0076] Table 13: Performance test results
[0077] From the data analysis of Table 13, it can be seen that after the optimization of the composition and process, the composite film prepared in this application has significantly high barrier properties. Figure 1~Figure 2 analyze, Figure 1 This is a schematic diagram of the structure of the high barrier composite film prepared in Example 1 of the present invention, which is a three-layer structure, including a first PE layer 1, a high barrier composite layer 2 and a second PE layer 3. Figure 2 The schematic diagram of the principle of carboxyl-terminated polyethylene glycol siloxane modified nano hydrotalcite in Example 1 of the present invention is shown in Figure 1. The surface of the nano hydrotalcite is modified by carboxyl-terminated polyethylene glycol siloxane to shield the surface hydroxyl groups. At the same time, the steric effect of the polyethylene glycol macromolecular chain segment is used to inhibit the aggregation of nano sheets and enhance their dispersibility. Only when the nano sheets are fully dispersed and peeled off in a single piece can the best barrier effect be guaranteed at the minimum dosage. Through the above method, the barrier coating still obtains a high barrier effect when the thickness is less than 5%.
[0078] In Comparative Example 1, since the barrier coating does not contain nano-hydrotalcite, the barrier effect is provided by the CPVA resin alone, and the barrier effect is limited, which is manifested as having higher OTR and WVTR.
[0079] In Comparative Example 2, since the components do not contain carboxyl-modified polyethylene, the barrier coating and the PE-based film lack reaction sites, and the two cannot produce a bonding effect. The barrier coating and the PE-based film have a large difference in polarity, the coating has poor adhesion, and the OTR and WVTR also increase.
[0080] In comparative example 3, since there is no crosslinking agent, the barrier coating and the PE base film are combined only by physical adsorption, the bonding force is low, and the coating adhesion is insufficient. In addition, CPVA cannot undergo a crosslinking reaction, resulting in a sharp increase in OTR and WVTR.
[0081] Comparative Example 4 uses conventional polyvinyl alcohol resin, which has poor bonding and compatibility with the non-polar PE base film, resulting in poor coating adhesion.
[0082] Comparative Example 5 does not contain carboxyl-terminated polyethylene glycol siloxane, and the nano-hydrotalcite is easily agglomerated, resulting in uneven dispersion, and cannot participate in the subsequent cross-linking reaction, which affects the bonding strength of the coating, and the OTR and WVTR also increase.
[0083] In Comparative Example 6, the base film was not subjected to a corona treatment process to further enhance the density of the surface carboxyl functional groups, and had fewer surface reaction sites. The coating adhesion was not as good as that of the embodiment, and the barrier performance was also insufficient.
[0084] Comparative Examples 7 and 8 limit the single-piece thickness and the single-piece average diameter-to-thickness ratio of the nano-hydrotalcite. Since the thickness of the hydrotalcite in the comparative examples is relatively large, the single-piece density decreases under the same mass, and the single-piece average diameter-to-thickness ratio is relatively small, the coverage is not as good as that of Example 1. If the single-piece average diameter-to-thickness ratio is greater than the limit value, it is easy to break during processing, resulting in a rapid decrease in the diameter-to-thickness ratio, which also leads to a decrease in coverage. Its barrier performance is not as good as that of Example 1 in terms of macroscopic performance.
[0085] In summary, compared with comparative examples 1-8, embodiments 1-5 of the present invention still have good coating adhesion when the coating thickness ratio does not exceed 5%, and have extremely low oxygen permeability and water vapor permeability, indicating that the embodiments have more excellent barrier properties and do not affect their recyclability.
[0086] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high barrier composite film, characterized in that: The high-barrier composite film comprises a first PE layer, a high-barrier coating layer and a second PE layer which are arranged in sequence, and the thickness of the first PE layer and the second PE layer respectively accounts for 20% to 79% of the total thickness of the high-barrier composite film, and the thickness of the high-barrier coating layer accounts for 1% to 5% of the total thickness of the high-barrier composite film; Wherein, the first PE layer and the second PE layer both include the following raw materials in parts by weight: 30 to 80 parts of PE resin, 20 to 70 parts of carboxyl-modified polyethylene, and 0.1 to 10 parts of auxiliary materials; The high barrier coating comprises the following raw materials in parts by weight: 100 parts of carboxyl-modified polyvinyl alcohol resin, 40 to 400 parts of nano-hydrotalcite, 1 to 80 parts of carboxyl-terminated polyethylene glycol siloxane, 3 to 12 parts of a crosslinking agent and 3 to 12 parts of an auxiliary agent.
2. The high barrier composite film according to claim 1, characterized in that: The melting index of the PE resin at 190° C. and 2.16 kg is in the range of 1 g / 10 min to 30 g / 10 min.
3. The high barrier composite film according to claim 1, characterized in that: The carboxyl-modified polyethylene is one or more of ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, acrylic acid grafted polyethylene and methacrylic acid grafted polyethylene.
4. The high barrier composite film according to claim 1, characterized in that: The auxiliary materials include one or more of antioxidants, anti-ultraviolet agents, plasticizers, flame retardants, nucleating agents and inorganic fillers.
5. The high barrier composite film according to claim 1, characterized in that: The carboxyl-modified polyvinyl alcohol resin has a weight average molecular weight of 60,000 g / moL to 300,000 g / moL, a degree of alcoholysis of 80% to 99%, and a mass fraction of carboxyl groups of 0.2% to 5%.
6. The high barrier composite film according to claim 1, characterized in that: The nano-hydrotalcite is an inorganic nano-sheet with a layered structure, the thickness of a single sheet is 6nm-20nm, and the average diameter-to-thickness ratio of a single sheet is 150-250.
7. The high barrier composite film according to claim 1, characterized in that: The weight average molecular weight of the polyethylene glycol segment of the carboxyl-terminated polyethylene glycol siloxane is 200 g / moL to 4000 g / moL; The chemical structural formula of the carboxyl-terminated polyethylene glycol siloxane is as follows: .
8. The high barrier composite film according to claim 1, characterized in that: The crosslinking agent is a multifunctional aziridine crosslinking agent, and the multifunctional aziridine crosslinking agent is one or more of trimethylolpropane-tris[3-(2-methylaziridinyl)]propionate, trimethylolpropane-tris(3-aziridinyl)propionate and pentaerythritol tris(3-aziridinyl)propionate.
9. The high barrier composite film according to claim 1, characterized in that: The auxiliary agent includes one or more of a defoamer, a leveling agent, an antioxidant, an anti-hydrolysis agent, and a UV absorber.
10. A method for preparing a high barrier composite film, characterized in that: The preparation method is used to prepare the high barrier composite film according to any one of claims 1 to 9, and the preparation method comprises the following steps: The raw materials for preparing the first PE layer are mixed evenly, melt-blended and extruded into granules in a twin-screw extruder to obtain a first PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a first PE layer base film; The raw materials for preparing the second PE layer are mixed uniformly, melt-blended and extruded into granules in a twin-screw extruder to obtain a second PE layer mixture, which is then melt-processed into a film and subjected to corona treatment to obtain a second PE layer base film; Dispersing a carboxyl-modified polyvinyl alcohol resin, a crosslinking agent and an auxiliary agent in an appropriate amount of water to obtain a carboxyl-modified polyvinyl alcohol aqueous dispersion; then dispersing nano-hydrotalcite and carboxyl-terminated polyethylene glycol siloxane in an appropriate amount of water, stirring at 50° C. to 80° C. for 6 h to 24 h to obtain a carboxyl-modified nano-hydrotalcite aqueous dispersion, and cooling to room temperature; and then adding the carboxyl-modified nano-hydrotalcite aqueous dispersion to the carboxyl-modified polyvinyl alcohol aqueous dispersion under stirring, adjusting the solid content within the range of 3% to 15%, to obtain a high barrier coating; The high barrier coating is coated on one side of the first PE layer base film and / or the second PE layer base film, and then the side coated with the high barrier coating is laminated, hot air dried at 60°C~105°C, and then aged at 45°C~80°C for 48h~72h to obtain a high barrier composite film.
Citation Information
Patent Citations
Long-acting barrier quality-guaranteeing food packaging material and manufacturing method thereof
CN101654165A
High-barrier polyving akohol coating for coating lined paper and preparation method thereof
CN103382677A
High-barrier coating material and preparation method thereof
CN118496719A
Container
JP1999348955A
Gas barrier composition, gas barrier film and method of manufacturing the same
JP2002060577A
Cited By
Multi-layer composite polyester base film structure with high weather resistance
CN120396481A
A multilayer composite polyester-based film structure with high weather resistance
CN120396481B